Сегментування української плодово-ягідної продукції на міжнародному ринку - Колокольчикова, Ірина Володимирівна; Kolokolchykova, Iryna (Запоріжжя : 2019, 2019)
UA: У статті розкрито сутність категорії «сегментування ринку» як процесу, виділено класичні підходи до принципів сегмен тування на національному рівні. Висвітлено основні напрями проникнення на світові ринки, які досліджували науковці. Доведено передумови розвитку міжнародного ринку, його перспектив. У процесі міжнародної сегментації ринку плодово-ягідної продукції вивчено досвід провідних вчених з цього питання, запропоновано концепцію міжнародного сегментування ринку плодів та ягід за відповідними блоками. Ця концепція разом з виділенням етапів включає блоки з обґрунтованим переліком показників оцінювання та змісту самого процесу сегментації. Проаналізовано сучасний стан розвитку експортно-імпортних операцій українських товаровиробників з міжнародним ринком фруктів та ягід, встановлено позитивні тенденції. EN: In the context of globalization of world markets, the forma tion of common approaches to the choice of the product by the consumer, the issues of expanding the boundaries of the national market of agricultural products become urgent. This also applies to the market of fruits and berries, which is now rapidly developing, increasing volumes. Ukrainian fruit market has all the prospects of successful functioning in the international market. The main methods of studying the process of segmentation of international fruit markets is a systematic and integrated approach to the stages of segmentation, taking into account the influence of all factors; monographic and statistical method for the analysis of export and import of fruits and berries in Ukraine 2018. The results of this study are the construction of the concept of segmentation of the international fruit market. The international segmentation process is divided into stages that create function blocks. At each stage, work is carried out to assess the host country’s market. Thus, at the first level, the international business environment of the exporting country is assessed in the context of political, legal, economic, cultural, social and technological indicators of the country’s development. The next step is to select the country or region for export. The last stage is connected with the process of segmen tation. International segmentation at the last stage can be both spatial and technological. Spatial segmentation can be offered as: concentration of efforts on one segment; selective concentration; specialization in a particular market, product specialization, and full coverage of the market. Technological segmentation takes into account the characteristics and requirements for the production of fruits and berries: either international standards or organic produc tion. Ukrainian producers are gradually moving to the requirements of international certification. The market of organic fruits is also growing; it has prospects and the appropriate legislative framework. The analysis of export import indicators in 2018 showed that the main exporters are Poland, Turkey and France. Among the food orientation-favorite today are nuts, citrus fruits and bananas.
Segmentation of ukrainian fruit and berry products in the international market
Keywords: сегмент; сегментація ринку; міжнародна сегментація; принципи сегментування; ринок плодово-ягідної продукції; експорт; імпорт; segment; market segmentation; international segmentation; segmentation principles; fruit and berry market; export; import